Ictal SPECT in Localizing Epileptogenesis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Ictal single-photon emission computed tomography (SPECT) was used successfully in the localization of an epileptic focus in two children, ages 9 and 7 years, with intractable epilepsy reported from the University of Alabama at Birmingham Epilepsy Center.